Metamorphic development of skarns at Pernstejn, Svratka Crystalline Complex, Bohemian Massif - Pertoldova,J.; Pertold,Z.; Pudilova,M. (Journal of the Czech Geological Society, 1998)
A study was carried out at Pernstejn (Svratka Crystalline Complex, Bohemian Massif) of the geological and metamorphic development of skarns in relation to the surrounding paraseries, orthogneisses and migmatites, from the standpoint of the geological structure, mineral association, mineral chemism, geothermometry, REE and oxygen isotopes. From a lithological and mineralogical point of view, the skarns form nonhomogeneous lenses, whose deformation is more complex than in the surrounding paraseries. The temperatures of formation of garnet-clinopyroxene-magnetite paragenesis of the skarns, 620 °C (710 °C) or 670 °C (640 °C), determined on the basis of the distribution of the major elements and oxygen isotopes amongst the coexisting phases, correspond to the conditions of peak metamorphism in the amphibolite facies. The rocks of the paraseries were metamorphosed under the same conditions, while the migmatites and metagranitoids exhibit lower temperatures 550-600 °C. The isotopic composition of oxygen in the skarn silicates is contradictory to concepts of contact metasomatic formation of skarns, connected with metagranitoids and migmatites. Oxygen also probably did not originate from the metamorphic solutions, which were in equilibrium with the paraseries. The REE distribution indicates the presence of solutions of a reducing nature and/or of high temperatures. It is our opinion that the precursors of the skarns were present in the paraseries from the very beginning, were metamorphosed together with gneisses and were probably formed in a sedimentary exhalative environment.
Keywords: skarn; metamorphism; geothermometry; oxygen and carbon isotopes; REE